The Effect Of Workload And Job Stress On Turnover Intention at CV. Gudang Cell Tasikmalaya - Priyanto, Arief Dwi; Karmila, Mila; Yusnita, Rita Tri (Universitas Dehasen Bengkulu, 2023)
This study aims to determine the effect of workload and work stress on turnover intention at CV. Gudang Cell Tasikmalaya. The research method used is quantitative, data obtained through questionnaires to employees of CV. Gudang Cell Tasikmalaya sales department as many as 45 respondents. Sample withdrawal using saturated samples and the analytical tool used is the path analysis method. The results showed that workload had a significant effect on work stress at CV. Gudang Cell Tasikmalaya. Workload does not have a significant effect on turnover intention at CV. Gudang Cell Tasikmalaya. Work stress has a significant effect on turnover intention at CV. Gudang Cell Tasikmalaya. Workload has a significant effect on turnover intention through job stress at CV. Gudang Cell Tasikmalaya.